Perceived workplace discrimination, coping and psychological distress among unskilled Indonesian migrant workers in Malaysia - Noor, Noraini M.; Shaker, Muhamad Nabil (Elsevier, 2017)
Migrant workers face many migration-related stressors that may affect their mental health.This study examines workplace discrimination in relation to psychological distress, and the role of coping among unskilled Indonesian migrant workers in Malaysia. In a sample of 119 workers (39 males and 80 females), results of a hierarchical regression analysis showed that workplace discrimination was positively related to psychological distress. Both problem-oriented coping and emotion/avoidance coping were predictive of distress. While problem-oriented coping was associated with lower distress, emotional/avoidance coping was related with higher distress levels. In addition, low emotion/avoidance coping was found to buffer the adverse effect of discrimination on distress. These results are discussed in relation to the literature on coping as well as the social-cultural context of the migrants and the host country.